The Combination of Image and Personification in Song Lyrics by Arya Galih: A Stylistic Study - Shinta Widya Palupi (Raja Zulkarnain Education Foundation, 2026)
A song is a literary work that possesses poetic qualities and is combined with music. Arya Galih is a singer and songwriter recognized for his distinctive vocal character and his ability to arrange words aesthetically. This study aims to describe the combination of imagery and personification in the lyrics of Arya Galih’s songs. The research employs a qualitative descriptive method. The object of the study is the lyrics of five songs by Arya Galih: Kobaring Asmara, Lereng Gunung Lawu, Sarangan Nglarung Rasa, Magetan Sewu Kenangan, and Esemu Semangatku, with a focus on the integration of imagery and personification. Data collection techniques include reading, note-taking, and literature review. Reading and note-taking were conducted by carefully and repeatedly examining Arya Galih’s lyrics, then recording sentences that indicate the presence of imagery and personification. Literature review involved analyzing various relevant sources related to imagery and personification in song lyrics. Data analysis was conducted using the model proposed by Miles and Huberman, which includes three stages: data reduction, data display, and conclusion drawing/verification. Data reduction involved selecting and filtering the relevant data, while data display was organized in the form of descriptive text, followed by drawing conclusions based on the presented data. The results of the study show that Arya Galih’s lyrics employ visual imagery, gustatory imagery, tactile imagery, and kinetic imagery. Among these, visual imagery appears most frequently. The study also indicates that the most prominent stylistic feature in his lyrics is the combination of imagery and personification. This combination enhances the poetic and expressive quality of his songs, allowing the lyrics to convey emotion and meaning vividly, while engaging listeners both intellectually and emotionally.